EMPOWERING COMMUNITY PARTICIPATION: SHAPING POLICY CHANGES IN INDIGENOUS VILLAGES' STRUCTURAL REGULATIONS IN ROKAN HULU, RIAU PROVINCE: - Data Wardana; Agung Wicaksono (Moderat : Jurnal Ilmiah Ilmu Pemerintahan, 2023)
This study delves into the significant role of community engagement in influencing policy changes within traditional villages, focusing on Regency Rokan Hulu, Riau Province. Employing qualitative methods such as interviews, observations, and discussions, the research sheds light on the impact of community input on policy formulation. The study reveals that when communities actively craft regulations for traditional villages, these regulations become more aligned with the community's aspirations and necessities. The data collection process involved thorough field visits, where researchers interacted with community members and stakeholders in policy-making. Findings underscore the transformative effect of community participation on policy outcomes. Communities play a crucial role in driving effective policy changes by collectively drafting profiles that articulate the essence of traditional villages and supporting governmental initiatives in their establishment. In conclusion, this study emphasises the integral role of community involvement in shaping policy changes within conventional village settings. In Regency Rokan Hulu, Riau Province, the collaborative approach between community engagement and policy formulation leads to regulations that genuinely resonate with the community's desires. Thus, embracing community participation is a pivotal factor for the successful evolution of policies impacting traditional villages.